Answer:
![\bold{((x+2)^2)/(4)+((x+1)^2)/(9)=1}](https://img.qammunity.org/2020/formulas/mathematics/high-school/60gwhqirtrd5u2uit1ecefaeapkzplyynx.png)
Explanation:
Put like terms together:
9x² + 36x + ____ + 4y² + 8y + ____ = -4 + ____ + ____
Complete the square for both terms:
9(x² + 4x + 4 ) + 4(y² + 2y + 1 ) = -4 + 9(4) + 4(1)
↓ ↑ ↓ ↑
= (2)²
= ( 1 )²
9(x + 2)² + 4(y + 1)² = 36
Divide everything by 36:
![(9(x+2)^2)/(36)+(4(y+1)^2)/(36)=(36)/(36)](https://img.qammunity.org/2020/formulas/mathematics/high-school/hdj4thsj7ijagze1ud6275tiapb0onjr0c.png)
Simplify:
![((x+2)^2)/(4)+((y+1)^2)/(9)=1](https://img.qammunity.org/2020/formulas/mathematics/high-school/uhv01gpqog8gw2qknb4nx4y33rgrfiq8kx.png)